Short- and long-term effects of perinatal phthalate exposures on metabolic pathways in the mouse liver. Issue 1 (23rd December 2020) - Neier, Kari; Montrose, Luke; Chen, Kathleen; Malloy, Maureen A; Jones, Tamara R; Svoboda, Laurie K; Harris, Craig; Song, Peter X K; Pennathur, Subramaniam; Sartor, Maureen A; Dolinoy, Dana C
Abstract: Phthalates have been demonstrated to interfere with metabolism, presumably by interacting with peroxisome proliferator-activated receptors (PPARs). However, mechanisms linking developmental phthalate exposures to long-term metabolic effects have not yet been elucidated. We investigated the hypothesis that developmental phthalate exposure has long-lasting impacts on PPAR target gene expression and DNA methylation to influence hepatic metabolic profiles across the life course. We utilized an established longitudinal mouse model of perinatal exposures to diethylhexyl phthalate and diisononyl phthalate, and a mixture of diethylhexyl phthalate+diisononyl phthalate. Exposure was through the diet and spanned from 2 weeks before mating until weaning at postnatal day 21 (PND21). Liver tissue was analyzed from the offspring of exposed and control mice at PND21 and in another cohort of exposed and control mice at 10 months of age. RNA-seq and pathway enrichment analyses indicated that acetyl-CoA metabolic processes were altered in diisononyl phthalate-exposed female livers at both PND21 and 10 months (FDR = 0.0018). Within the pathway, all 13 significant genes were potential PPAR target genes. Promoter DNA methylation was altered at three candidate genes, but persistent effects were only observed for Fasn . Targeted metabolomics indicated that phthalate-exposed females had decreased acetyl-CoA at PND21 and increased acetyl-CoA and acylcarnitines at 10 months. Together, our data suggested that perinatal phthalate exposures were associated with short- and long-term activation of PPAR target genes, which manifested as increased fatty acid production in early postnatal life and increased fatty acid oxidation in adulthood. This presents a novel molecular pathway linking developmental phthalate exposures and metabolic health outcomes.